The Role of Managerial Accounting in Improving Efficiency and Profitability of SMEs: A Case Study of LKPs in Kampung Inggris Pare - Putri, Mita Oktavia; Lilik Purwanti (International Journal of Economics, Business and Innovation Research, 2025)
Micro, Small, and Medium Enterprises (UMKM) play a significant role in Indonesia’s economy, contributing 60.5% to the Gross Domestic Product (GDP) and absorbing around 96.9% of the workforce. Among the various sectors, Lembaga Kursus dan Pelatihan (LKP) in Kampung Inggris Pare has contributed to the development of the education sector, specifically in English language learning. Despite their importance, many LKP face challenges in managing finances, particularly in cost management and profitability. The lack of structured managerial accounting systems has hindered the ability of LKP to plan budgets, control operational costs, and set accurate course prices. This study aims to examine the role of managerial accounting in improving the efficiency and profitability of LKP in Kampung Inggris Pare. The research employs a qualitative approach using case studies to explore the challenges LKP face in managing costs and how managerial accounting can help address these challenges. Findings show that while many LKP still use traditional methods and face barriers in implementing effective accounting systems, those who have integrated managerial accounting practices have shown improvements in cost control and pricing strategies. This study highlights the importance of adopting managerial accounting to help LKP optimize cost management, set more accurate prices, and ultimately increase profitability. The results provide valuable insights for LKP managers, policy makers, and organizations aiming to improve financial literacy and managerial accounting practices in small businesses. Keywords: Managerial accounting, UMKM, Kampung Inggris Pare, efficiency, profitability